CONCEPTUALIZATION OF TAX BASE EXPANSION IN INDONESIA - Suparno Suparno (Journal Philosophy of Law, 2023)
This study aims to expand the tax base in Indonesia by looking at the data integration plan between the National Identity Number and Taxpayer Identification Number in the Harmonization of Tax Laws and Regulations. This research is included in normative juridical research by studying or analyzing secondary data in the form of primary, secondary, and tertiary legal materials by understanding law as a set of rules or positive norms in the statutory system that regulates human life. The research results show that the legal construction in Indonesia has not yet been explained to what extent and how the data integration of the two identity numbers is, but the purpose of this data integration is, of course, to enrich the tax database. On an ongoing basis, of course, it will increase voluntary compliance from taxpayers and increase state revenue from the taxation sector.